Effects of Presentation Slides on Students Attention and Visual Fatigue in Teaching Scenarios - Ho, YongIl; Mun, JongHyong (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study aimed to investigate the effects of visual and information characteristics of presentation slides, including font size, background–font contrast, and screen height, on students’ attention and visual fatigue in teaching scenarios, as well as to provide evidence-based recommendations for optimizing presentation design in educational settings. With the increasing reliance on electronic presentation slides in contemporary teaching, prolonged visual exposure has raised concerns regarding visual discomfort and reduced learning attention among students. Using a controlled teaching context, this study examined how variations in slide design influence visual fatigue symptoms and sustained attention during instructional sessions. The findings indicate that optimizing presentation slides with a font size of at least 28 points, light-absorbing backgrounds such as blue or green combined with light-emitting fonts such as white or yellow, and a screen height of 150 cm effectively reduces visual fatigue while maintaining stable levels of student attention in teaching scenarios. In addition, the integration of brief inter-class eye and musculoskeletal exercises further enhances the effectiveness of optimized slide design by alleviating cumulative visual and postural strain. Overall, the results demonstrate that appropriate visual design characteristics, when combined with simple physical interventions, play a significant role in promoting students’ visual comfort and attentional stability. These findings provide practical and evidence-based guidelines for educators and institutions to improve visual health, learning sustainability, and overall teaching efficiency in digitally mediated educational environments.